Motion capture, animation, previsualization and virtual production for The Unknown Patient (VR interactive short film) - J Vincent; P Divers; R Burt; D Czarnecki; T Ingram; K Wallace; S Hallgren; J Furler (2018)
DML inventions applied to an industry application, in the creation of this creative product. The Unknown Patient is a Virtual Reality, interactive short film that was selected for premiere at the highly prestigious Venice Film Festival.